Rural students’ perspectives of blended learning educational reform in Malaysia - Soo Kum Yoke; Nur Izzah Jamil; Faizah Abd Majid; Cuong Huy Pham; Siti Nur Aleesah Mohd Rosley (Institute of Advanced Engineering and Science, 2026)
Blended learning has become increasingly important in education reform, especially after the COVID-19 pandemic. This case study examines how rural students perceive blended learning towards education reform in Malaysia through a semi-structured interview with 20 students from a selected rural school in Malaysia. Thematic analysis applied to the research found that students had positive views of blended learning, appreciating its flexibility, potential to ensure equitable education, and ability to motivate learning, besides contributing to better educational outcomes and supporting government efforts to reform education. However, students identified several challenges to the implementation of blended learning, such as difficulty focusing on online lessons, unstable internet, and limited comprehension of blended learning. There were mixed responses to the necessity of education reform, with the majority opting for unnecessary or unsure. Hence, this study recommends a versatile learning model integrating online and face-to-face education to better support rural students and ensure an inclusive, equitable, and effective education system.